ASSESSMENT OF NATURAL-RESOURCE FACTOR OF GEOPOLITICAL SECURITY OF THE REPUBLIC OF KAZAKHSTAN - R.A. Karatabanov,; K.M. Dzhanalieva, (Academic Journal of Physical and Chemical Sciences, 2019)
Modern geo-ecological problems of Kazakhstan have different origins and varying degrees of severity, determining to a large extent the level of sustainability of PCS and the viability of the population. To determine the sustainability threshold of spatial-territorial formations, zonal, azonal and intrazonal groups of environmental problems were systematized, which are clearly manifested in the form of areas in the country. The presence of natural resources is an important factor that determines, among other things, the ability of the state to defend its independence and interests, and strengthens its strength in the negotiation processes. Also, the availability of a resource base determines the attractiveness of one country for another, and therefore it is important to assess the natural resource factor within the framework of Kazakhstan’s geopolitical security.